Aesthetics and Art Traditional and Contemporary China in a Comparative Perspective - Gao, Jianping (China Academic Library,, 2018)
This book introduces traditional and modern aesthetics and arts, comparing the similarities and differences between traditional and modern Chinese aesthetics. It also explores the aesthetic implications of traditional Chinese paintings, and discusses the development of aesthetics throughout history, as well as the changes and improvements in Chinese aesthetics in the context of globalization.